Allocation of public resources for Health in Macaé between 2014 and 2017: Reflections and Challenges - Silos Alves, Natália; de Souza Serio dos Santos, Danielle Maria; Fernandes de Souza, Jéssica; Reis e Silva, Rebeca; Piassi Dias Godói, Isabella (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Aim: To demonstrate the allocation of resources destined for the Health Financing Blocks transferred by the National Health Fund to the municipality of Macaé between 2014 and 2017. Methods: Descriptive quantitative study, based on the extraction and tabulation of available data of the Information System on Public Health Budgets (SIOPS), as well as publications including the Pluriannual Plan (2014-2017) of the municipality of Macaé. Results: The data extracted from the SIOPS, referring to FNS transfers, a total of R$174,860,780.76 was found to be allocated to health in Macaé, of which R$5,457,773.14 (3, 12%) directed to Pharmaceutical Assistance and R$ 40,467,477.50 (23.14%) to Primary Care in the period between 2014 and 2017. The data analyzed demonstrate that Macaé implemented, in particular, in the years of 2015 and 2016 resources below than foreseen by the Pluriannual Plan (2014-2017), which may be associated with the oil crisis experienced by the municipality. It should be noted that the loss in tax collection can directly impact the feasibility of offering health services, which can be considered critical and fragile since many individuals are dependent on the SUS. Conclusion: It is important to understand the real demands and the rational planning of health needs by local managers, so that even in times of budgetary crisis they can organize themselves to better promote and offer the services considered essential to their population.